2013
DOI: 10.1111/1750-3841.12073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Locust Bean Gum and Mono‐ and Diglyceride Concentrations on Particle Size and Melting Rates of Ice Cream

Abstract: The objective of this study was to determine how varying concentrations of the stabilizer, locust bean gum (LBG), and different levels of the emulsifier, mono- and diglycerides (MDGs), influenced fat aggregation and melting characteristics of ice cream. Ice creams were made containing MDGs and LBG singly and in combination at concentrations ranging between 0.0% to 0.14% and 0.0% to 0.23%, respectively. Particle size analysis, conducted on both the mixes and ice cream, and melting rate testing on the ice cream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Muse and Hartel () and Bolliger et al. () found that increasing the amount of polysorbate 80 (PS80) decreased melt rate significantly, while increasing amount of mono‐ and diglycerides also decreased melt rate, but to a less extent (Cropper et al., ). An increased fat destabilization was seen with the increasing level of emulsifiers added in ice cream (Bolliger et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Muse and Hartel () and Bolliger et al. () found that increasing the amount of polysorbate 80 (PS80) decreased melt rate significantly, while increasing amount of mono‐ and diglycerides also decreased melt rate, but to a less extent (Cropper et al., ). An increased fat destabilization was seen with the increasing level of emulsifiers added in ice cream (Bolliger et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In food industry, LBG alone or in combination with other hydrocolloids (e.g. carrageenan, xanthan gum, guar gum) is widely used in beverages (Dogan et al 2011), bakery products (Kohajdová et al 2009), noodles (Pan et al 2016), dairy products (Cropper et al 2013) and as edible coatings (Martins et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The food additive mono-and diglycerides of fatty acids offers the food industry many solutions for optimal product formulation and processing. When used as additive in food products such as bread and baked products and ice cream, monoand diglycerides of fatty acids require a high concentration of monoglycerides [57,58]. The high interest of the food industry in the utilisation of mono-and diglycerides of fatty acid additives is due to the fact they are safe for consumption and have useful properties that improve the production of food products [59].…”
Section: Common Uses For Mono-and Diglycerides Of Fatty Acidsmentioning
confidence: 99%